ESTABLISHING VALUES OF CHARACTER IN PHYSICAL EDUCATION LEARNING - Firman, Bafirman (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Establishing character values at school has been done through variety of subjects including physical education. The values established only touch on the investment of the values not on the application in daily life yet. The research is characterized by research and development with qualitative and quantitative method. The expert validators; physical Education learning, phsycolog of learning analysis, and Indonesian language. The experiment design is pre test â€“ post test controlled group design. The population is the elementary school students in Padang and the sample and respondent are detrmined through purposive sampling, that is: SDcore (core elementary school) and SD impacted (impacted elementary school) with 123 students of fifth grade. Collecting data is by using questionaire, observation, and interview. Data analysis is trhough descriptive statistical data in which the hypothesis is examined by covariance analysis and t-test. The research finding, (1) the establishing values influence significantly in physical Education learning for fifth grade students at SD core and impacted, (2) the establishing values affects significantly in physical Educationlearning between modificated and conventional model for fifth grade students of SD core and impacted.Â 